PROMOTING FUN LEARNING IN GRAMMAR CLASS THROUGH SONGS - Nuraeningsih Nuraeningsih (Vision: Journal for Language and Foreign Language Learning, 2014)
Many teachers present grammar in a conventional way. The rules are taught in a very formal situation with monotonous activities. Many times they need repetition to make students really understand about a topic, especially when they teach tenses. It is important for students to be able to distinguish each type of them. This brings about students’ boredom and discourages them to get involved, so that unconscious learning doesn’t occur. However, songs promote relaxed, enchanted atmosphere in classrooms. Furthermore, songs are perceived to stimulate students’ interest in learning. By having that fun, conducive learning atmosphere, students may feel excited in joining grammar class. This paper aims at providing basic conceptual arguments of the advantage of using songs in teaching grammar. It also discusses the pedagogical implication of utilizing songs to create joyful class. The procedure of teaching grammar through songs is then proposed.